Analisis Gaya Hidup, Kualitas Produk, dan Kualitas Pelayanan terhadap Keputusan Pembelian pada Sejawad Warkop Kota Binjai (Jurnal Ekonomi Bisnis dan Akuntansi, 2025)
Recently, several business sectors in Indonesia have developed very rapidly, one of which is the food and beverage business, especially in the coffee shop business. Various coffee shops have sprung up in various regions, including in Binjai City, one of which is Sejawad Warkop. Increasingly fierce competition encourages business actors to understand the factors that influence consumer purchasing decisions. This study is aimed at examining the influence of lifestyle, product quality, and service quality both partially and simultaneously on purchasing decisions at Sejawad Warkop Binjai City. The research method used was descriptive quantitative with a sample of 100 respondents. Respondents were determined by the criteria of customers who had bought coffee at Sejawad Warkop, Binjai City. The research instrument was in the form of a questionnaire with a Likert scale and the data were analyzed using multiple linear regression tests. The results of the study show that lifestyle variables, product quality, and service quality partially or simultaneously have a significant effect on purchasing decisions. The magnitude of the influence of independent variables on purchasing decisions was 73.1%, while the remaining 26.9% was influenced by other factors outside of the study, such as promotion, price, and location. This research is expected to make a practical contribution for the management of Sejawad Warkop in formulating a more targeted marketing strategy and become a reference for further research related to consumer behavior in the coffee shop business sector.